Instrumento de coleta de dados de enfermagem para o idoso em situação de violência - Bezerra, Elismar Pedroza (2021)
Introduction: Violence against senior citizens is continuously growing. They are frequently exposed to a variety of abuses, including within family environment. This way, nursing plays a prominent role in assisting such population. Nursing assistance must occur in a way to meet individuals’s needs, so as to provide a good quality care.Therefore, a Nursing data collecting instrument, based on scientific evidence can contribute for supporting and systematizing the elderly’s assistance in case of violence. Thus, its use will allow not only identification and assistance in the individual’s needs, but also it will establish more effective communication between nursing professionals and health care users. Aims: Identifying empirical indicators to be used when meeting the nursing professional; proposing a nursing data collecting instrument to the elderly in violence condition; validating the instrument contents. Methodology: this is a study conducted in three stages: integrative literature review carried out in 05 data bases: WEB of Science, MEDLINE/PubMed, Scopus,Cumulative Index to Nursing and Allied Health Literature,as well as Nursing Data Base; construction and validation of nursing data collecting instrument for senior citizens in violence condition ( methodological study). Results: the main empirical indicators included in the instrument have involved the basic human needs, among them the regulation of the general, neurological and vascular status; the need for oxygenation, hydration and elimination; body mechanics; motility, nutrition and sexuality, among others; signs and symptoms of violence including physical, psychological, financial, sexual damages, as well as abandonment. During the validation period of the instrument, it reached a general means of the Index of Contents Validity above 0,80 in all domains. Therefore, experts have recommended its application. Discussion: In order to meet the considerations by judges, as well as to improve the instrument quality, adjustments and complements in the protocol were made, concerning the following items: regulation of elderly people’s general status; vascular regulation need; need for skin-mucosa integrity; need for thermal regulation and security. FINAL Considerations: we expect that the instrument can contribute to the Nursing Services, concerning Nursing assistance systematizing, strategy organization of assistance and knowledge about the subject, by supporting professionals’ practice, particularly those who work with old age patients facing violence situations. This will make it possible the decrease of impacts caused by such issue, as well as the improvement of senior citizens’ well-being.